2014
DOI: 10.3324/haematol.2014.116715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the revised International Prognostic Scoring System, cytogenetics and monosomal karyotype on outcome after allogeneic stem cell transplantation for myelodysplastic syndromes and secondary acute myeloid leukemia evolving from myelodysplastic syndromes: a retrospective multicenter study of the European Society of Blood and Marrow Transplantation

Abstract: ABSTRACTnetic risk classification entered the revised IPSS (IPSS-R) scoring system for patients with MDS, which was renewed in 2012 accordingly. 18 The impact of the revised IPSS-R for MDS patients undergoing SCT was analyzed in one single center study, 13 and more recently in a national multicenter study.14 These studies have shown that the novel classification has greater discriminating power for OS and relapse after SCT than the old IPSS classification. In contrast to the latter studies, we focused only on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 31 publications
(47 reference statements)
4
24
0
Order By: Relevance
“…Similarly, a CIBMTR study showed relapse rates in the order of 25-28% and higher in patients with poor risk cytogenetic abnormalities or patient who underwent NMA conditioning regimen 43 . Relapse strongly correlated in our series with cytogenetic risk at diagnosis, similarly to what has been published for patients undergoing unmodified transplant in a large retrospective study reported by EBMT 44 . Patients with poor risk cytogenetic abnormalities had a relapse rate of 31% at 1 year compared to only 17% in patients with intermediate risk and 8% in patients with low risk.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, a CIBMTR study showed relapse rates in the order of 25-28% and higher in patients with poor risk cytogenetic abnormalities or patient who underwent NMA conditioning regimen 43 . Relapse strongly correlated in our series with cytogenetic risk at diagnosis, similarly to what has been published for patients undergoing unmodified transplant in a large retrospective study reported by EBMT 44 . Patients with poor risk cytogenetic abnormalities had a relapse rate of 31% at 1 year compared to only 17% in patients with intermediate risk and 8% in patients with low risk.…”
Section: Discussionsupporting
confidence: 87%
“…The revised IPSS confirmed poor prognosis for the very poor cytogenetics category (40). MK+MDS after allogeneic HCT has been described with similar poor outcomes (4144). The current analysis also demonstrated that MK+MDS were associated with higher TRM, in contrast to the models in AML in which the cytogenetic group had no impact on TRM.…”
Section: Discussionmentioning
confidence: 95%
“…Smaller single centre studies described dismal outcome of transformed MPN and CMML (Mesa et al , ). Reports about allo‐HSCT in transformed leukaemia are mainly published regarding the preceding haematological disease such as MDS (Koenecke et al , ), MPN (Lussana et al , ), CMML (Symeonidis et al , ) or aplastic anaemia (Hussein et al , ). Larger systematic reports are lacking.…”
Section: Discussionmentioning
confidence: 99%